2001 Special Merit Award: Robert J. Collins, DMD, MPH - Dushanka V. Kleinman, DDS, MScD (Blackwell Synergy, 2001)
This year we are fortunate to have two recipients of the AAPHD Special Merit Award: Dr. Robert J. C o l h and Dr. Caswell A. Evans. This award is presented to individuals for their special meritorious service to public health dentistry and for their tireless efforts on behalf of the nation’s health and AAPHD’s goals. Let me begin in alphabetical order.